Global action plan for childhood diarrhoea: Developing research priorities: Report from a Workshop of the Programme for Global Paediatric Research. - Zipursky, Alvin; Wazny, Kerri; Black, Robert; Keenan, William; Duggan, Christopher; Olness, Karen; Simon, Jonathan; Simpson, Evan; Sherman, Philip; Santosham, Mathuram; Bhutta, Zulfiqar A (Journal of Global Health, 2013)
Background: Childhood diarrhoea remains a major public health problem responsible for the deaths of approximately 800 000 children annually, worldwide. The present study was undertaken to further define research priorities for the prevention and treatment of diarrhoea in low and middle income countries. We used the Child Health and Nutrition Research Initiative (CHNRI) process for defining research priorities. This provided a transparent, systematic method of obtaining the opinions of experts regarding research priorities in childhood diarrhoea. The present report describes the deliberations of a workshop that reviewed these research priorities by stakeholders including colleagues from: government agencies, academic institutions, major funding agencies and non-governmental organizations.Methods: The workshop included 38 participants, divided into four groups to consider issues in the categories of description, delivery, development and discovery. Each group received 20 to 23 questions/research priorities previously identified by the CHNRI process. Deliberations and conclusions of each group were summarized in separate reports that were further discussed in a plenary session including all workshop participants.Results: THE REPORTS OF THE WORKING GROUPS EMPHASIZED THE FOLLOWING FIVE KEY POINTS: 1) A common theme was the need to substantially increase the use of oral rehydration salts (ORS) and zinc in the prevention and treatment of diarrhoea. There is a need for better definitions of those factors that supported and interfered with the use of these agents; 2) There is an urgent need to determine the long-term effects of chronic and recurrent bouts of diarrhoea on the physical and intellectual development of affected children; 3) Improvements in water, sanitation and hygiene facilities are critical steps required to reduce the incidence and severity of childhood diarrhoea; 4)Risk factors enhancing the susceptibility and clinical response to diarrhoea were explored; implementation research of modifiable factors is urgently required; 5) More research is required to better understand the causes and pathophysiology of various forms of enteropathy and to define the methods and techniques necessary for their accurate study.Conclusions: The participants in this workshop determined that use of the CHNRI process had successfully defined those research priorities necessary for the study of childhood diarrhoea. The deliberations of the workshop brought these research priorities to the attention of stakeholders responsible for the implementation of the recommendations. It was concluded that the deliberations of the workshop positively supplemented the research priorities developed by the CHNRI process.